Framing of issues across actors: exploring competing discourses in digital arenas. Issue 2 (2nd May 2017) - Ravazzani, Silvia; Maier, Carmen Daniela
Abstract : Purpose: The purpose of this paper is to show how the strategic selection of discursive and interactive strategies generates specific framings of an issue to advocate opposite positions, embodying a struggle of power between parties with their own agendas. Design/methodology/approach: Drawing on literature within framing, digital issue arenas and critical discourse, this study analyses qualitative hypermodal data retrieved from two websites: Protect Mauna Kea, and Maunakea and Thirty Meter Telescope. These two websites frame the internationally renowned telescope's construction on Mauna Kea Mountain in Hawaii from alternative perspectives. Findings: On each website, frame articulation attempts to connect the event to specific concerns, values and beliefs in order to construct alternative versions of reality which can possibly fit with those of supporters. Simultaneously, this is reinforced by frame amplification concretized in selected discursive and interactive strategies that highlight or downplay the issue from particular perspectives. Originality/value: The study offers a deep insight into the complexity and dynamic nature of framing, in particular into how framing can vary and compete across actors. It also responds to "the need for critical awareness of discourse in contemporary society" (Fairclough, 2010, p. 554) by revealing how the power positions of "challengers and powerholders" (Steinberg, 1998, p. 846) are discursively reproduced and reinforced through distinctive discursive and interactive strategies. Finally, this study adopts a critical approach to hypermodal discourse.